Pengaruh Pengetahuan Kewirausahaan, Family Environment, dan Penggunaan Media Sosial Terhadap Minat Berwirausaha Mahasiswa - Budiarti, Kharisma Wahyu; Maslichah, Maslichah; Rudiningtyas, Dyah Arini (Universitas Islam Malang, 2024)
This research aims to examine the influence of entrepreneurial knowledge, family environment, and the use of social media on the entrepreneurial interest of Malang Islamic University students class of 2020 who have passed the entrepreneurship course. Entrepreneurial knowledge, family environment, and use of social media are considered as independent variables, while students' entrepreneurial interest is the dependent variable. The research methodology used in this research is quantitative by utilizing numerical data. Primary data was collected through questionnaires. The target population was Malang Islamic University students, with the sample size determined using the Malhotra formula to obtain 85 respondents. The hypothesis was tested through various statistical analyzes including descriptive statistics, instrument testing, normality test, classical assumption test, moderated regression analysis, and hypothesis testing using SPSS Version 25. The findings showed that entrepreneurial knowledge, family environment, and use of social media had an influence on students' entrepreneurial interest.Keywords: Entrepreneurial knowledge, family environment, use of social media, entrepreneurial interest